2021
DOI: 10.3390/rs13061072
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval and Mapping of Soil Organic Carbon Using Sentinel-2A Spectral Images from Bare Cropland in Autumn

Abstract: Soil is the largest carbon reservoir on the terrestrial surface. Soil organic carbon (SOC) not only regulates global climate change, but also indicates soil fertility level in croplands. SOC prediction based on remote sensing images has generated great interest in the research field of digital soil mapping. The short revisiting time and wide spectral bands available from Sentinel-2A (S2A) remote sensing data can provide a useful data resource for soil property prediction. However, dense soil surface coverage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 64 publications
2
22
0
Order By: Relevance
“…Therefore, vegetation indices derived from remotely sensed data, soil moisture and brightness indices can represent vegetation biomass and soil characteristics [ 36 , 68 ]. Wang, K. found NDVI, BI, BI2 and SATVI to be the most important variables for predicting farmland SOC in autumn [ 69 ], which is consistent with the results of this paper. Due to the sensitivity of SAVI to soil properties [ 70 ], it is considered the most important variable in agricultural soil organic carbon prediction.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, vegetation indices derived from remotely sensed data, soil moisture and brightness indices can represent vegetation biomass and soil characteristics [ 36 , 68 ]. Wang, K. found NDVI, BI, BI2 and SATVI to be the most important variables for predicting farmland SOC in autumn [ 69 ], which is consistent with the results of this paper. Due to the sensitivity of SAVI to soil properties [ 70 ], it is considered the most important variable in agricultural soil organic carbon prediction.…”
Section: Discussionsupporting
confidence: 90%
“…Madugundu et al: Soil organic carbon estimation using satellite images relationship between VIs and SOC. In this study, linear relationships between the SWIR-1 band, VI from the L8 and S2A satellite data were observed against the SOC and were A confirmed with a similar study by Wang et al (2021). The analysis of S2A data showed that the two SWIR broad bands centered at 1610 and 2190 nm are sufficient to satisfactorily predict SOC content, as a result, high values of BSI and low RSR areas were associated with low SOC areas, and vice versa.…”
Section: Soc Prediction Models -Performancesupporting
confidence: 89%
“…While, vegetation indices (VI), such as the Normalized Difference Vegetation Index (NDVI), NDVIRedEdge, Enhanced Vegetation Index (EVI), Bare Soil Index (BSI), and Reduced Simple Ratio (RSR) were computed and subsequently used for the development of SOC prediction models. ) employed on satellite images such as Landsat (Viscarra-Rossel and Bouma, 2016;Kumar et al, 2016), Sentinel-2 (Wang et al, 2021;Dvorakova et al, 2021), etc. Many studies have been conducted to investigate the characteristics of soil spectral reflection in regions of moderate to high soil fertility levels, but studies in low-fertility soils are still limited in the Arab region, such as Saudi Arabia.…”
mentioning
confidence: 99%
“…This is due to the combination of several factors linked with the sensor characteristic (range and spectral resolution) and the distance between the sensor and target surface (atmospheric disturbance, signal quality, spectral and spatial resolution), and the soil surface conditions (moisture, roughness, vegetation residues). Despite this, many recent scientific papers demonstrated the capability of the Copernicus Sentinel-2 Multi-Spectral Instrument (MSI) (hereinafter referred to as S2) and NASA Landsat-8 Operational Land Imager (OLI) (hereinafter referred to as L8) optical data for soil properties prediction and mapping [15][16][17][18][19][20][21], obtaining encouraging results, especially for the SOC content.…”
Section: Introductionmentioning
confidence: 99%